COVID-19 PANDEMIC IMPACT ON HYDROPONIC LETTUCE BUSINESS INCOME OF MURIA FARM KUDUS - Rheza Ivan Farrell (Jurnal Ekonomi Pertanian dan Agribisnis, 2022)
The impact of covid-19 pandemic was experienced in almost every business sector, including the hydroponic lettuce sector at Muria Farm Kudus. Since most consumers of hydroponic lettuce are businesses in the culinary sector that are affected by the implementation of lockdown and social distancing, causing restaurants, cafes, and restaurants to be limited seated or unable to fully operate. This study aimed to analyze business income and profitability before and during the Covid-19 pandemic and analyze whether there are differences in the level of business income and business profitability before and during the Covid-19 pandemic. The research method was a case study with a quantitative approach with purposive site selection. The study was conducted using secondary data related to the company's costs, sales, and revenue as well as primary data by interviewing using a questionnaire and determining respondents purposively. The method of data analysis was quantitative descriptive using the calculation of Total Cost, Total Revenue, and Net Revenue and profitability using the calculation of Gross Profit Margin and Net Profit Margin. The data were then analyzed using Kolmogorov-Smirnov normality test and independent sample t test. The results showed that there is no significant difference between Muria Farm's hydroponic lettuce business income before and during the Covid-19 pandemic however there is a significant difference between business profitability before and during the Covid-19 pandemic.